Additive Manufacturing for Nanogenerators: Fundamental Mechanisms, Recent Advancements, and Future Prospects - Tian, Zhiyu; Tsui, Gary Chi‑Pong; Tang, Yuk‑Ming; Wong, Chi‑Ho; Tang, Chak‑Yin; Ko, Chi‑Chiu (Nano-Micro Letters, 2025)
Additive manufacturing (AM), with its high flexibility, cost-effectiveness, and customization, significantly accelerates the advancement of nanogenerators, contributing to sustainable energy solutions and the Internet of Things. In this review, an in-depth analysis of AM for piezoelectric and triboelectric nanogenerators is presented from the perspectives of fundamental mechanisms, recent advancements, and future prospects. It highlights AM-enabled advantages of versatility across materials, structural topology optimization, microstructure design, and integrated printing, which enhance critical performance indicators of nanogenerators, such as surface charge density and piezoelectric constant, thereby improving device performance compared to conventional fabrication. Common AM techniques for nanogenerators, including fused deposition modeling, direct ink writing, stereolithography, and digital light processing, are systematically examined in terms of their working principles, improved metrics (output voltage/current, power density), theoretical explanation, and application scopes. Hierarchical relationships connecting AM technologies with performance optimization and applications of nanogenerators are elucidated, providing a solid foundation for advancements in energy harvesting, self-powered sensors, wearable devices, and human–machine interaction. Furthermore, the challenges related to fabrication quality, cross-scale manufacturing, processing efficiency, and industrial deployment are critically discussed. Finally, the future prospects of AM for nanogenerators are explored, aiming to foster continuous progress and innovation in this field. Highlights: 1 The advantages of additive manufacturing for nanogenerators are firstly examined from the perspective of underlying mechanisms coupled with theoretical explanations, providing critical insights into enhancing output performance and expanding applications. 2 Recent advancements in additive manufacturing for nanogenerators are systematically reviewed, emphasizing the characteristics of common technologies, their application scopes, and their impacts on nanogenerator performance metrics. 3 The current challenges and future prospects of additive manufacturing for nanogenerators are explored, aiming to promote continuous advancements in this field.